Pendampingan Belajar Siswa melalui Model PjBL: Proyek Pembuatan Barcode sebagai Sumber Belajar Klasifikasi Tumbuhan - Ihsan, Afifi Raima; Jumrodah Jumrodah; Yenny Erawaty (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
To overcome the students' lack of knowledge about local plants around the school, this mentoring uses a project-based learning model (PjBL) with the aim of accompanying them in a plant barcode making project that is carried out for 4 months. As a technology-based learning medium, students make observations, identify plants, species and make barcodes containing information about plants. Student activities before, during, and after the project are described through a qualitative research approach. The result is that project-based learning successfully improves students' creativity, engagement, critical thinking, and cooperation skills. Additionally, students gain a better understanding of biodiversity through this project, and they can use technology to provide engaging and relevant lessons.